Functional neurological disorder in Europe: regional differences in education and health policy - Serranová, Tereza; Di Vico, Ilaria; Tinazzi, Michele; Aybek, Selma; Bilic, Ervina; Binzer, Stefanie; Bøen, Erlend; Bruggeman, Arnout; Bratanov, Christo; Cabreira, Veronica Raquel Alheia; Golder, Dawn; Dunalska, Anna; et al. (European journal of neurology, 2024)
BACKGROUND: Functional neurological disorder (FND) is a common cause of neurological disability. Despite recent advances in pathophysiological understanding and treatments, application of this knowledge to clinical practice is variable and limited. OBJECTIVE: Our aim was to provide an expert overview of the state of affairs of FND practice across Europe, focusing on education and training, access to specialized care, reimbursement and disability policies, and academic and patient-led representation of people with FND. METHODS: We conducted a survey across Europe, featuring one expert per country. We asked experts to compare training and services for people with FND to those provided to people with multiple sclerosis (MS). RESULTS: Responses from 25 countries revealed that only five included FND as a mandatory part of neurological training, while teaching about MS was uniformly included. FND was part of final neurology examinations in 3/17 countries, unlike MS that was included in all 17. Seventeen countries reported neurologists with an interest in FND but the estimated mean ratio of FND-interested neurologists to MS neurologists was 1:20. FND coding varied, with psychiatric coding for FND impacting treatment access and disability benefits in the majority of countries. Twenty countries reported services refusing to see FND patients. Eight countries reported an FND special interest group or network; 11 reported patient-led organizations. CONCLUSIONS: FND is largely a marginal topic within European neurology training and there is limited access to specialized care and disability benefits for people with FND across Europe. We discuss how this issue can be addressed at an academic, healthcare and patient organization level.
Keywords: Multiple Sclerosis; zdravotní politika; dostupnost zdravotnických služeb; nemoci nervového systému; neurologové; Evropa; Neurologists; lidé; roztroušená skleróza; Health Services Accessibility; Nervous System Diseases; Health Policy; Humans; neurologie; Neurology; Europe